IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM MENCIPTAKAN SUASANA KONDUSIF DI SMA NEGERI 3 PALU - Thalib Thalib; Bahrun Bahrun (ISTIQRA, 2014)
Multicultural education is a form of education that are expected to shape the behavior of learners of character or morality. In the National Education Law No. 20, 2003, namely: national education aims to develop students' potentials to become a man of faith and devoted to God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become citizens of a democratic and responsible. Correspondingly, reinforced in national education functions to develop the skills and character development as well as a dignified civilization in order to educate the nation. Therefore, multicultural education is expected to provide color on the behavior of learners who have an awareness of cultural diversity, human rights and the reduction or elimination of the type of prejudice to a fair public life and advanced society. Therefore, multicultural education is expected to be implemented in school education, so that it becomes a character for students who are able to appreciate and respect the diversity of cultures, races, and religions which ultimately can create a conducive atmosphere in the school